PENGARUH MANAJEMEN KELAS TERHADAP MINAT BELAJAR SISWA KELAS XII IPA V SMA DARUSSALAM BLOKAGUNG TEGALSARI BANYUWANGI TAHUN PEMBELAJARAN 2020/2021 - Nurkafid Nizam Fahmi; Hasan Abdul Wafi (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
Abstract Education has an important role in a country. Through quality education a country can look to its future. In this study focused on classroom management, interest in learning at the Darussalam High School in Tegalsari Banyuwangi Blockagung, related to this, the author tried to answer two main questions, namely: (1) Is there an influence of Class Management on Student Interest in Class X1I IPA V SMA Darussalam Blokagung Tegalsari Banyuwangi Year 2019/2020 Learning (2) How big is the Effect of Class Management on the Learning Interest of Class X1I Science V students in SMA Darussalam Blokagung Tegalsari Banyuwangi 2019/2020 Learning Year. This study uses quantitative descriptive methods with simple linear regression analysis techniques. The study population was a number of students in the Darussalam High School Blokagung Tegalsari Banyuwangi. To measure variables, researchers used observations, questionnaires and documentation. In testing the validity of the instrument, researchers used a simple linear regression analysis formula.After analyzing the data collected, it was found that (1) there was an effect of Class Management on the Learning Interest of Class X1I Science V SMA SMA Darussalam. (2) the effect of Class Management on Student Interest in Class X1I Natural Sciences V of SMA Darussalam BlokagungTegalsariBanyuwangi is strong with a value of 97,2% and the remaining 2,8% is influenced by other variables.